2022
DOI: 10.1002/asia.202200179
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Molecule Classification of Aspartic Acid and Leucine by Molecular Recognition through Hydrogen Bonding and Time‐Series Analysis

Abstract: Amino acid detection/identification methods are important for understanding biological systems. In this study, we developed single-molecule measurements for investigating quantum tunneling enhancement by chemical modification and carried out machine learning-based time series analysis for developing accurate amino acid discrimination. We performed single-molecule measurement of L-aspartic acid (Asp) and L-leucine (Leu) with a mercaptoacetic acid (MAA) chemical modified nano-gap. The measured current was invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…We previously demonstrated that modifying nanogap electrodes improves identification accuracy, even for molecules that cannot be distinguished using conventional machine learning methods alone. 36 Further progress in both statistical analysis method and novel and precise measurement technique development will be necessary to achieve these goals.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…We previously demonstrated that modifying nanogap electrodes improves identification accuracy, even for molecules that cannot be distinguished using conventional machine learning methods alone. 36 Further progress in both statistical analysis method and novel and precise measurement technique development will be necessary to achieve these goals.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…[22][23][24] The research of single-molecule measurements has developed to successfully measure the conductance of nucleotides in DNA and RNA [25][26][27][28][29][30] and amino acids. [31][32][33][34][35][36][37] As the nature of single-molecule measurements allows for the measurement of the direct conductance of a single molecule, they are expected to flourish as a new analytical method that is highly sensitive, rapid, and requires no pre-treatment steps. Furthermore, singlemolecule measurements play a crucial role in the investigating of novel physical and chemical properties in the nanoscale.…”
Section: Introductionmentioning
confidence: 99%
“…To address the above challenges, some highly parallel, single-molecule techniques have been envisioned in the past decade for next-generation protein analysis and sequencing. 17,18 These emerging methods use tunneling currents, 19,20 fluorescence, 21 resistive-pulse nanopores, 3,22,23 and other nanotechnologies to sequence or identify individual proteins, down to the single-molecule level or in single cells. 24,25 The precision of these advanced measurement tools have the capacity to create many opportunities in biomedical research, with applications ranging from proteomics of single cells and bodily fluids to sensing and classifying low-abundance protein biomarkers for disease screening and precision diagnostics.…”
Section: Introductionmentioning
confidence: 99%
“…To address the above challenges, some highly parallel, single-molecule techniques have been envisioned in the past decade for next-generation protein analysis and sequencing. , These emerging methods use tunneling currents, , fluorescence, resistive-pulse nanopores, ,, and other nanotechnologies to sequence or identify individual proteins, down to the single-molecule level or in single cells. , The precision of these advanced measurement tools have the capacity to create many opportunities in biomedical research, with applications ranging from proteomics of single cells and bodily fluids to sensing and classifying low-abundance protein biomarkers for disease screening and precision diagnostics . Among the methods driving this era of advanced nanodevices for single-molecule recognition was the tunneling current method, as reported by Zwolak and Di Ventra for DNA sequencing. This method was expanded to detect AAs using two metal electrodes separated by a nanogap (0.7–2 nm), comparable to the size of typical AA molecules.…”
Section: Introductionmentioning
confidence: 99%
“…In that approach, a probed molecule, positioned between two nanoelectrodes, could be detected by measuring the electric tunneling current. [22][23][24][25][26][27][28][29] There are two distinct approaches: (i) a molecule has no covalent bonds with electrodes (employed in DNA 22,23,30,31 or protein sequencing 24,25 ), and (ii) a molecule is covalently bound to one 26 or both electrodes (similar to molecular diodes [27][28][29] ). Although covalent bonds between the molecule and the electrodes are convenient for stable electronic transport, such sensors would need frequent chemical or thermal treatment for trapped TATP molecules cleaning.…”
Section: Introductionmentioning
confidence: 99%